"Everybody Loved Each Other There": Roma Memories of the One-Time Cinka Panna Colony in Oradea and Its Liquidation during the Communist Times. Issue 4 (November 2018) - Plainer, Zsuzsa
This article is part of the special cluster titled Social practices of remembering and forgetting of the communist past in Central and Eastern Europe, guest edited by Malgorzata Glowacka-Grajper This study deals with the liquidation of a Roma colony from the Romanian town of Oradea during the 1970s. Colony life, as well as the process of removal, demolition of the houses, and relocation of the inhabitants into blocks of flats, is mainly grasped through Roma narratives collected from 2011 onwards. But here we do not narrow down remembering communism to a mere collection of untold stories from the past. Based on the framework developed by Maria Todorova for the study of remembering communism, the following questions are addressed: How is the pre-1989 condition of the Roma revealed through their narratives? What do these say about the condition of the Roma during state socialism? How do past events influence the present-day marginalization of the group? A comparison of the socialist and post-socialist conditions of the Roma could be considered an important issue in forming an account of this ethno-racial group in Eastern Europe. It is so, as—despite the current research, which is small in number, various interpretations exist, raising the demand for scholars to address this issue.